Noctuoidea (Lepidoptera) from Cyprus with descriptions of larvae of some species - Ahola, Matti (Entomologica Fennica, 1998)
A list of species collected is presented with notes on collecting sites. Larvae of Agrochola orientalis Fibiger, 1997 Agrochola lychnidis (Denis & Schiffermüller, 1775), Ammoconia aholai Fibiger, 1996, Allophyes asiatica (Staudinger, 1892) and Polymixis trisignata (Ménétriés, 1847) are described and illustrated. Comparative comments with some closely related species are given.